2011
DOI: 10.21608/eajbsc.2011.16140
|View full text |Cite
|
Sign up to set email alerts
|

Physiological studies on the effect of a bradykinin potentiating factor (BPF) isolated from scorpion venom on the burnt skin of alloxan-induced diabetic Guinea pigs.

Abstract: It is well known that, Wound healing in the diabetes is enormous, growing problem and having cost Medicaid. Therefore, this study produces an exciting prospect, to improve diabetic burn healing, and evaluates the ability of a bradykinin potentiating factor (BPF) isolated from scorpion venom (Buthus occitanus) in treatment of burns in diabetic male Guinea pigs. Male Guinea pigs of approximate (550 g body weight each) were divided into five groups. In the normal group; Guinea pigs were interaperitoneally (i.p) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In recent years, NO has emerged as a critical molecule in wound healing, where it increases collagen content in experimental wounds (Thornton et al, 1998 andShi et al, 2000). It is worth to mention that, in other study the wound healing in diabetic guinea pigs are improved by injection of bradykinin potentiating factor (BPF) which is the stimulator of NO (Elshater et al, 2011). So in this study, the burned skin healing in guinea pigs are improved by propolis.…”
Section: Effect Of Treatment With Propolis or Silver Sulfadiazine (Ssmentioning
confidence: 75%
“…In recent years, NO has emerged as a critical molecule in wound healing, where it increases collagen content in experimental wounds (Thornton et al, 1998 andShi et al, 2000). It is worth to mention that, in other study the wound healing in diabetic guinea pigs are improved by injection of bradykinin potentiating factor (BPF) which is the stimulator of NO (Elshater et al, 2011). So in this study, the burned skin healing in guinea pigs are improved by propolis.…”
Section: Effect Of Treatment With Propolis or Silver Sulfadiazine (Ssmentioning
confidence: 75%
“…It is estimated that a considerable number of cancer patients receive radiation therapy during their course of illness [154]. However, radiation therapy might lead to side effects, including radiation-induced heart disease (RIHD) in patients having lymphoma, breast, lung, and esophageal cancer [155,156]. It has been demonstrated that BPPs obtained from L. quinquestriatus improved cardiomyopathy induced by γ-radiation in rats, probably by acting as a scavenger of free radicals to protect the heart from negative effects derived from radiation exposure [157].…”
Section: Bradykinin-potentiating Effectsmentioning
confidence: 99%